2002
DOI: 10.1021/ma020387l
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Synthesis of Dendritic Poly(amide-urea)s via Curtius Rearrangement. 1. Monomer Syntheses and Model Reactions for the Dendritic Poly(amide-urea)s Synthesis

Abstract: The syntheses of two AB2 monomers, aminodicarboxylic acid (1) and aminodicarbonyl azide (2), and their model reactions for the one-pot synthesis of dendritic aromatic poly(urea-amide)s using the two AB2 monomers were carried out. The model reaction of 2 and p-tolyl isocyanate produced the target urea with two acyl azide groups in 93% yield at 25 °C for 30 min in tetrahydrofuran (THF). The Curtius rearrangement from an acyl azide to an isocyanate was completed at 140 °C for 30 min in THF. The isocyanate produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…Similar to the concept presented by Kumar and Meijer, Okaniwa et al published a related A 2 B building block for branched polyurea synthesis (Figure ). The preparation involves 5 steps, however, the overall yield cannot be specified from the information given in the paper.…”
Section: Synthetic Concepts Toward Hyperbranched Polyurea Structuresmentioning
confidence: 79%
“…Similar to the concept presented by Kumar and Meijer, Okaniwa et al published a related A 2 B building block for branched polyurea synthesis (Figure ). The preparation involves 5 steps, however, the overall yield cannot be specified from the information given in the paper.…”
Section: Synthetic Concepts Toward Hyperbranched Polyurea Structuresmentioning
confidence: 79%
“…2 was heated in toluene during which it undergoes Curtius rearrangement to form CHDI. The conversion of azide to isocyanate was confirmed by FTIR studies 30. CHDI was directly reacted with TCD‐DM in DMAc at 80 °C to yield polyurethane P‐1 .…”
Section: Resultsmentioning
confidence: 89%
“…After 0.5 h of the reaction, an aliquot of the reaction mixture was submitted for FTIR analysis. By comparing the FTIR spectra of the acyl azide and the isocyanate, it was found that the peak at 2141 cm −1 corresponding to the CON 3 group is vanished and a new peak at 2261 cm −1 corresponding to the NCO group was observed, which confirmed the formation of isocyanate 30. The clear solution was cooled to –20 °C using an ice–salt bath, and a mixture of TCD‐DM (0.36 g, 1.80 mmol, for polymer P‐1 ) and DBTDL (2 drops) in dry DMAc (2 mL) was added dropwise.…”
Section: Methodsmentioning
confidence: 89%
“…135 More recently, Gody et al used the Curtius rearrangement on an azide containing RAFT agent, and the reaction between an amine and an isocyanate for polymer-polymer coupling. 136 Additionally, the Curtius rearrangement has been further utilized in the afore-mentioned synthesis of dendritic/hyperbranched polymers using blocked isocyanates, with Okaniwa and co-workers producing dendritic poly(amide-urea)s, 137 and Sivakumar and Nasar synthesizing amine and hydroxyl terminated hyperbranched polyurethanes. 138 Another application was shown by Sagi et al who used a blocked isocyanate polymer backbone to produce self-immolative polymers able to be used as molecular sensors.…”
Section: Reaction Mediummentioning
confidence: 99%